2015
DOI: 10.1002/cssc.201501116
|View full text |Cite
|
Sign up to set email alerts
|

Seawater as Alternative to Freshwater in Pretreatment of Date Palm Residues for Bioethanol Production in Coastal and/or Arid Areas

Abstract: The large water consumption (1.9-5.9 m(3) water per m(3) of biofuel) required by biomass processing plants has become an emerging concern, which is particularly critical in arid/semiarid regions. Seawater, as a widely available water source, could be an interesting option. This work was to study the technical feasibility of using seawater to replace freshwater in the pretreatment of date palm leaflets, a lignocellulosic biomass from arid regions, for bioethanol production. It was shown that leaflets pretreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 57 publications
0
26
0
7
Order By: Relevance
“…It has been estimated that the production of bioethanol in cellulosic biorefineries consumes 1.9-5.8 gallons of freshwater per gallon of bioethanol produced [57,58]. Alternatively, concentrated seawater, representing 97% of the Earth's total water, could represent a cost-effective solution in order to decrease the large volume of used freshwater [59]. Moreover, it would save around 800-2400 million liters of fresh water annually for a biorefinery, which produces 400 million liters of ethanol per year, leading to a reduction in freshwater reservoirs shortening.…”
Section: Challenges Of Cellulases Cocktailsmentioning
confidence: 99%
“…It has been estimated that the production of bioethanol in cellulosic biorefineries consumes 1.9-5.8 gallons of freshwater per gallon of bioethanol produced [57,58]. Alternatively, concentrated seawater, representing 97% of the Earth's total water, could represent a cost-effective solution in order to decrease the large volume of used freshwater [59]. Moreover, it would save around 800-2400 million liters of fresh water annually for a biorefinery, which produces 400 million liters of ethanol per year, leading to a reduction in freshwater reservoirs shortening.…”
Section: Challenges Of Cellulases Cocktailsmentioning
confidence: 99%
“…Regarding a large amount of freshwater consumption, it has been reported that there is no significant difference between the growth of S. cerevisiae on freshwater or in seawater during growth on pretreated date palm leaflets . Studies have shown that Halomonas campaniensis ( H. campaniensis ) is able to grow in artificial seawater for poly(3‐hydroxybutyrate) (PHB) production and the seawater can also be used for xylose dehydration to form furfural .…”
Section: Next‐generation Industrial Biotechnologymentioning
confidence: 99%
“…Seawater, an inexhaustible water source, could be an option for bioproduction. It was reported that no significant difference was observed for growth of Saccharomyces cerevisiae on freshwater or seawater pretreatment of date palm leaflets for bioethanol production . The possibility of using seawater could at least reduce concerns that ethanol production could waste a lot of precious fresh water.…”
Section: Advantages Of Halophiles As a Chassismentioning
confidence: 99%